Specific particularities of Science and Technology research labor - Ha, Mai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
S&T research labor is a specific field of labor. The study of specific particularities of this field falls within the scope of social studies. S&T research labor is an effective tool that is capable of creating strong driving forces if a healthy environment for social development is harvested. If the innovative environment is hindered, the S&T features have no room to develop to their full potential. Instead, they would become decorative objects or even tools for profit seeking individuals. The objective of this paper is to identify social aspects and specific particularities of S&T research labor. Then some conclusions will be made on the ways where S&T policies for sustainable development in Vietnam can enhance the endogenous potential of S&T workers. Code: 11040803